Avian adrenal medulla : cytomorphology and function - Ghosh, Asok; Carmichael, Stephen W.; Mukherjee, Monisha (Acta Biologica Szegediensis, 2001)
The purpose of this review is to explore the world literature on the avian adrenal medulla from the last 20 years. Unlike the mammalian adrenal medulla, the adrenal gland in birds has chromaffin cells mixed with cortical cells. Studies have investigated the ultrastructure (both transmission and scanning electron microscopy), biochemistry, and physiology (partic-ularly interactions with other endocrine glands) of the avian adrenal medulla. Although progress has been made, it is apparent that research on the avian adrenal medulla still lags behind work on the mammalian organ.